Meningkatkan Kemampuan Menggambar Berdasarkan Contoh dengan Metode Penugasan pada Anak Kelompok B di Taman Kanak-Kanak Syaloom Ende - Lebe Wele; Marta Kala (Prima Magistra: Jurnal Ilmiah Kependidikan, 2020)
This study aims to uncover and describe: (1) Implementation of method of assignment in learning to draw in group B children in TKK Syalom, Ende, (2) The ability to draw children in group B in TKK Syalom after the assignment method is applied. This research is a class action research (CAR) implemented in 2 cycles. The data collection techniques used are observation and documentation. The subjects of this research were 19 children in group B. The results showed that; (1) The assignment learning method has been applied well in drawing learning for group B children in TTK Syaloom Ende. The observation results proved that in cycle I the implementation rate was 75% with good category and in cycle II increased to be very good with percentage of 90%, (2) The ability to draw children increased after the assignment method was applied to group B children in TKK Syaloom. This can be seen from the observation results on the pre-cycle, for the newly developed children, there were 6 children, children who start to grow, there were 10 children, children develop according to expectations were 3 children and for children who grow very well is no one. In the I cycle, of 19 peoples, for a newly developed child is no one, children who start developing were 9 peoples, children who thrive as expected were 8 children and grow very well were 2 children. In cycle II increased from 19 children, to the newly developed no one, for which began to grow there was also no one, for children who grew very well were 7 children and grew as expected were 12 people. Based on these results it can be concluded that the use of assignment methods can improve drawing skills.